PHARMACOTHERAPY EXACERBATIONS OF CHRONIC INFLAMMATORY CONDITIONS OF FEMALE GENITAL SPHERE USING TO GEPON AND LONGIDAZA - Svetlana Abramova; Galina Lazareva (Belgorod National Research University, 2016)
Researches of the last years showed that changes of local immunity at inflammatory diseases of appendages at women, to be exact a condition of a secondary immunodeficiency at the local level, arising against the main pathological process, are a consequence of an immune inflammation, violation of structure and function of cellular membranes because of lipid peroxidation. Research objective was establishment of changes of the metabolic status at an aggravation chronic salpingoophoritis and detection of efficiency of use in «Gepon's» complex pharmacotherapy and «Longidaza's» various medicinal forms. For this purpose under continuous supervision was the 70th women aged from 20 till 35 years with the established diagnosis chronic salpingoophoritis in an aggravation stage. All patients were divided into four groups according to age, minimum satellite, severity of illness and providing treatment. The first experimental group was included 18 patients with chronic adnexitis in the exacerbation phase, where the standard therapy. The second group was included patients (17 women), which put on «Longidaza» in the form of suppositories (1 suppository 3000 per recti 1 times a day for 5 days). In the third group (18 patients), patients received, in addition to a standard treatment regimen «Gepon» (10 mg per 1 times a day for 5 days). The fourth group was included patients (17 women), which put on «Longidaza» injections (1 suppository 3000 intramuscularly 1 time per day for 5 days). As a result of a research efficiency of use of immunocorrective preparations («Gepon» and «Longidaza») at patients chronic salpingoofority in an aggravation stage in correction of metabolic frustration is established. «Longidaza's» use in the form of candles has corrective and normalizing impact on the broken indicators of the metabolic status at patients chronic salpingoophoritis at local level whereas purpose of an injection form of this preparation normalizes parameters of the oxidatic status at system level. Results of a research allow to draw a conclusion that application in complex pharmacotherapy of patients with chronic salpingoophoritis longidaza and gepon in comparison with standard treatment makes more expressed impact on clinical picture of disease and laboratory indicators at system and local levels, thus maximum efficiency possesses a preparation of longidaza in the form of injections.